The Influence of Internal Audit Scope and Internal Auditors’ Experience on Internal Audit Effectiveness in Omani Public Sector - Dhiaa Shamki; Thuraiya Amur Alhajri (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
The purpose of the study is to present empirical evidence on the influence of the internal audit scope and internal auditor’s experience on the internal audit effectiveness. Employing questionnaire including four sections with 48 questions for responds of 163 employees in Public Authority for Social Insurance (PASI) in the Sultanate of Oman, descriptive analysis, correlation analysis, and multiple regressions were employed to examine the relationships among the selected three variables. The study found that a significant relationship between internal audit effectiveness and its scope and auditors’ experience. The findings suggest that awareness has to be maximized on employees to better cooperate with internal audit staff to improve the applications of internal audit standards. Managers are well interested in the organization’s activities and performance depending on the internal audit findings and observations.